ANALISIS MINAT INVESTOR KOTA MATARAM TERHADAP INVESTASI PADA PASAR MODAL SYARIAH - Naili Rahmawati (UIN Mataram, 2017)
This study has a background that the Mataram City as a religious city hasthe potential for the development of sharia investment, especially thesyariah capital market.This research conducted on investors domiciledin Mataram City at West Nusa Tenggara Province. The quantitativeanalysis method used in this research and descriptive method ofresearch data presented in the form of graphs or tables. There aretwo most decisive significant factors against the interest of investorsto invest in sharia investment. Firstly, the earning in investment shariasecurities is Halal. Secondly, the marketing force of the Capital Marketwho do not have sufficient knowledge about Sharia Capital Market.Based on that results and analysis of the research, it can be concludedthat the majority of investors in Mataram City interested to invest inIslamic capital market.